1979
DOI: 10.1084/jem.149.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The role of H-2 and Ia antigens in graft-versus-host reactions (GVHR). Presence of host alloantigens on donor cells after GVHR and suppression of GVHR with an anti-Ia antiserum against hose Ia antigens.

Abstract: By using an indirect immunofluorescence technique, the presence of host cell derived H-2K, H-2D, and Ia alloantigens on donor cells recovered from recipient spleens after a graft-versus-host response (GVHR) was demonstrated. Mapping studies indicated that only host K, D, and I-A region gene products could be identified on the donor cells. Host I-E/C- and I-J-subregion products were not absorbed by donor cells. Treatment of activated donor cells with anti-Ly sera plus C' revealed that donor cells carrying host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
5
16
0
Order By: Relevance
“…A potentiating effect of selective CD80 blockade was again difficult to detect due to the profound elimination of host B cell, even at the reduced donor cell inoculum, and is better seen in the chronic GVHD model. It should be noted that detection of donor T cells by flow cytometry becomes difficult after 2 wk in untreated acute GVHD mice, due to an overall down-modulation of MHC expression (26) and/or acquisition of host MHC by donor cells (27) that parallels disease severity (28). We interpret the reduced numbers of donor CD8 ϩ T cells at 2 wk in anti-CD80 mAb-treated mice (compared with control Ig-treated or untreated acute GVHD) to be a reflection of accelerated GVHD-associated MHC down-regulation rather than impaired engraftment and milder disease.…”
Section: Cd80 And/or Cd86 Blockade In Acute Gvhd Mimics the Effects Smentioning
confidence: 99%
“…A potentiating effect of selective CD80 blockade was again difficult to detect due to the profound elimination of host B cell, even at the reduced donor cell inoculum, and is better seen in the chronic GVHD model. It should be noted that detection of donor T cells by flow cytometry becomes difficult after 2 wk in untreated acute GVHD mice, due to an overall down-modulation of MHC expression (26) and/or acquisition of host MHC by donor cells (27) that parallels disease severity (28). We interpret the reduced numbers of donor CD8 ϩ T cells at 2 wk in anti-CD80 mAb-treated mice (compared with control Ig-treated or untreated acute GVHD) to be a reflection of accelerated GVHD-associated MHC down-regulation rather than impaired engraftment and milder disease.…”
Section: Cd80 And/or Cd86 Blockade In Acute Gvhd Mimics the Effects Smentioning
confidence: 99%
“…it is interesting to speculate that antigen transfer could be a biologically important mechanism for cell communication. It was recently reported that antigen transfer plays a role in the graft-versus-host-reaction (GvH) [12]. Preud'homme et al [12] found host alloantigens on donor cells after GvH.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that antigen transfer plays a role in the graft-versus-host-reaction (GvH) [12]. Preud'homme et al [12] found host alloantigens on donor cells after GvH. These alloantigens were H-2K, H-2D, and la, and it was possible to suppress the GvH by daily injections of anti-la sera.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, induction of the antitumor activity was abolished by administration of anti I-A a antibody, which caused a decline in Ia-positive macrophages in the peritoneal cavity, at the time of tumor antigen injection. In studies by others, in vivo administration of anti-Ia antibody was shown to cause inhibition of delayed type-hypersensitivity to a tumor-specific antigen [20], antibody production [25,26], and graftversus-host reactions [21]. However the relationship be-220 tween inhibition of these responses and Ia-positive cells was not clear.…”
Section: Discussionmentioning
confidence: 96%